Answer to Question #213691 in Differential Equations for anuj

Question #213691

Solve the equations by the use of the operator D







D²y -6Dy +9y= e^3x + e^-3x



1
Expert's answer
2021-07-19T14:34:05-0400

The homogeneous equation


"L(y)=(D^2-6D+9)y=0"

"(D-3)^2y=0"

The general solution of the homogeneous equation is

"y_h=(A+Bx)e^{3x}"

Find the particular equation.


"L(D)y=e^{3x}"

"L(D)=(D^2-6D+9)=(D-3)^2" has "3" as a double root. Then


"y_1=\\dfrac{x^2e^{3x}}{L''(3)}=\\dfrac{x^2e^{3x}}{2}"

"L(D)y=e^{-3x}"

"y_2=\\dfrac{e^{-3x}}{L(-3)}=\\dfrac{e^{-3x}}{(-3-3)^2}=\\dfrac{e^{-3x}}{36}"


"y_p=y_1+y_2=\\dfrac{x^2e^{3x}}{2}+\\dfrac{e^{-3x}}{36}"

The general solution of the nonhomogeneous equation is

"y=(A+Bx)e^{3x}+\\dfrac{x^2e^{3x}}{2}+\\dfrac{e^{-3x}}{36}"





Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog